Neutrophils as Orchestrators in Tumor Development and Metastasis Formation - Kalafati, Lydia; Mitroulis, Ioannis; Verginis, Panayotis; Chavakis, Triantafyllos; Kourtzelis, Ioannis (Frontiers in Oncology, 2020)
Several lines of clinical and experimental evidence suggest that immune cell plasticity is a central player in tumorigenesis, tumor progression, and metastasis formation. Neutrophils are able to promote or inhibit tumor growth. Through their interaction with tumor cells or their crosstalk with other immune cell subsets in the tumor microenvironment, they modulate tumor cell survival. Here, we summarize current knowledge with regards to the mechanisms that underlie neutrophil–mediated effects on tumor establishment and metastasis development. We also discuss the tumor-mediated effects on granulopoiesis and neutrophil precursors in the bone marrow and the involvement of neutrophils in anti-tumor therapeutic modalities.